Encyclopedia of archival science - Duranti, Luciana; Franks, Patricia C. 1945- (Lanham, Maryland Rowman & Littlefield, 2015)
"Here is the first-ever comprehensive guide to archival principles and practices. Encyclopedia of Archival Science features 130 entries which cover every aspect of the profession. These entries range from the traditional basics (like appraisal and provenance) to today's necessities (digitization and digital curation). You'll also find biographies of the leading luminaries from archival history like Ernst Posner, Margaret Cross-Norton, and Philip Brooks. Historical and ethical components of practice are infused throughout the work"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Archives -- Encyclopedias; Records -- Management -- Encyclopedias